Community-Based Health Interventions for Climate Resilience: Empowering Local Communities through Adaptation and Public Health Strategies - Zani, Benny Novico; Zahir, Roya; Raza, Amir (Journal of Multidisciplinary Sustainability Asean, 2026)
Background. Climate change poses escalating risks to public health, particularly for communities with limited adaptive capacity and high exposure to environmental hazards. Community-based health interventions have emerged as a promising approach to enhance climate resilience by integrating local knowledge, participatory governance, and context-sensitive public health strategies. These interventions shift the focus from top-down responses to locally driven adaptation, positioning communities as active agents in managing climate-related health risks. Purpose. This study aims to examine the effectiveness of community-based health interventions in strengthening climate resilience and empowering local communities through integrated adaptation and public health strategies. The research seeks to identify key mechanisms, outcomes, and enabling conditions that support sustainable and equitable health resilience at the community level. Method. A qualitative analytical design was employed, utilizing an integrative review of peer-reviewed literature, policy documents, and selected case studies related to community-based climate-health initiatives. Data were analyzed thematically to assess intervention models, governance structures, community participation, and health outcomes. Results. The findings indicate that community-based interventions enhance adaptive capacity by improving health awareness, strengthening social capital, and fostering locally relevant adaptation practices. Programs that combine public health services, environmental management, and community engagement demonstrate greater effectiveness in reducing vulnerability to climate-related health risks. Conclusion. The study concludes that community-based health interventions represent a critical pathway for achieving climate resilience. Empowering local communities through participatory and integrated strategies not only improves health outcomes but also supports sustainable and inclusive climate adaptation efforts.